(untitled) (ResearchJet Journal of Analysis and Inventions, 2022)
This article discusses the influence of individual typological features on the learning activities of students. Also, information is provided on psychological difficulties in communicating with students, overcoming these difficulties and the importance of organizing the educational process, taking into account the individual characteristics of students.